Effects of steam curing regimes on the capillary water absorption of concrete: Prediction using multivariable regression models. (30th September 2020) - Liu, Baoju; Shi, Jinyan; Zhou, Feng; Shen, Shuai; Ding, Yibo; Qin, Jiali
Highlights: The influence of steam curing parameters on the sorptivity coefficient of steam-cured concrete is investigated. Surface treatments of concrete before the heating stage are helpful to reduce the capillary water absorption. Multivariable regression models can predict sorptivity coefficient of steam-cured concretes by steam curing parameters. Abstract: Effects of steam curing parameters on the capillary water absorption (CWA) of concrete are investigated, and the models related to steam curing parameters for predicting the sorptivity coefficient of concrete are developed using extensive experimental database. The results show that the CWA and sorptivity coefficient of steam-cured concrete is closely related to the steam curing regimes and the surface condition of concrete. Longer precuring time or lower heating rate can reduce the CWA and sorptivity coefficient of steam-cured concrete. When the treatment time is 8 h, higher and lower treatment temperature can increase the CWA and sorptivity coefficient of concrete. When the treatment temperature is 60 ℃, the CWA and sorptivity coefficient of concrete increase with the treatment time. Highest cooling rate will lead to highest sorptivity coefficient of steam-cured concrete. The CWA and sorptivity coefficient of top surface are higher than that of side surface, and the CWA and sorptivity coefficient of surface concrete are higher than that of the interior concrete. In addition, the surface treatment methods of quadric-plastering and covering film can reduce the CWA and sorptivity coefficient of concrete. Finally, linear regression analysis and multiple nonlinear regression are employed to simulate the sorptivity coefficient of steam-cured concrete. The multivariable regression analysis method gives an explicit formula that achieves a good predictive result.